Behavior of corroded bonded partially prestressed concrete beams - Mohamed Moawad; Anwar Mahmoud; Hossam El-karmoty; Ashraf El zanaty (HBRC Journal, 2018)
Prestressed concrete is widely used in the construction industry in buildings. And corrosion of reinforcing steel is one of the most important and prevalent mechanisms of deterioration for concrete structures. Consequently the capacity of post-tension elements decreased after exposure to corrosion. This study presents results of the experimental investigation of the performance and the behavior of partially prestressed beams, with 40 and 80 MPa compressive strength exposed to corrosion. The experimental program of this study consisted of six partially prestressed beams with overall dimensions equal to 150 × 400 × 4500 mm. The variables were considered in terms of concrete compressive strength, and corrosion location effect. The mode of failure, and strain of steel reinforcement, cracking, yield, ultimate load and the corresponding deflection of each beam, and crack width and distribution were recorded. The results showed that the partially prestressed beam with 80 MPa compressive strength has higher resistance to corrosion exposure than that of partially prestressed concrete beam with 40 MPa compressive strength. Not big difference in deterioration against fully/partially corrosion exposure found between partially prestressed beams at the same compressive strength. The most of deterioration incident in partially prestressed beam acts on non prestressed steel reinforcement. Because the bonded tendons are less likely to corrode, cement grout and duct act as a barrier to moisture and chloride penetration, especially plastic duct without splices and connections. The theoretical analysis based on strain compatibility and force equilibrium gave a good prediction of the deformational behavior for high/normal partially prestressed beams. Keywords: Beam, Corrosion, Deterioration, Partially prestressed, High strength concrete